2005
DOI: 10.1016/j.chemosphere.2004.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metal oxides on PCDD/Fs formation from pentachlorophenol

Abstract: The total suppressing efficiencies of several metal oxides including CaO, BaO, PbO, Ag 2 O, HgO and SnO which have lower Z/r (charge to radius ratio) <2 are all over 90%. The theories of generalized acid-base and atomic parameter (Z/r) were used to speculate the effecting mechanisms. The factors including time and temperature on suppressing efficiencies of CaO, BaO and PbO have also been studied in the present paper. The results showed that the total suppressing efficiencies of CaO, BaO and PbO increase with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Pentachlorophenol (PCP) was purified to remove PCDE and PCDD/F impurities (Qian et al 2005). Prior to the experiments, the silicon dioxide was Soxhlet extracted with toluene, air-dried at room temperature, and then heated at 700°C for 6 h. The copper oxide was ground in a mortar before use.…”
Section: Methodsmentioning
confidence: 99%
“…Pentachlorophenol (PCP) was purified to remove PCDE and PCDD/F impurities (Qian et al 2005). Prior to the experiments, the silicon dioxide was Soxhlet extracted with toluene, air-dried at room temperature, and then heated at 700°C for 6 h. The copper oxide was ground in a mortar before use.…”
Section: Methodsmentioning
confidence: 99%
“…To the contrary, the existence of Pb (chloride and oxide) and Ca (oxide) might inhibit the formation of PCDD/Fs (Qian et al, 2005;Fujimori et al, 2009). But for Al, conflict roles (i.e., either act as a catalyst or inhibitor) have been found in PCDD/F formation processes (Hinton and Lane, 1991;Gullett et al, 1992;Qian et al, 2005). In this study, the co-existence of the above five metal contents warrants the need for further investigation in their roles on PCDD/F formation processes.…”
Section: Ionic Constituents Containing In Wb Dustsmentioning
confidence: 93%
“…Among these five metal contents, several studies have shown that the existence of Fe and K might lead to the increase in PCDD/Fs formation (Hinton and Lane, 1991;Nganai et al, 2009;Fujimori et al, 2009). To the contrary, the existence of Pb (chloride and oxide) and Ca (oxide) might inhibit the formation of PCDD/Fs (Qian et al, 2005;Fujimori et al, 2009). But for Al, conflict roles (i.e., either act as a catalyst or inhibitor) have been found in PCDD/F formation processes (Hinton and Lane, 1991;Gullett et al, 1992;Qian et al, 2005).…”
Section: Ionic Constituents Containing In Wb Dustsmentioning
confidence: 99%
“…Various chemical inhibitors for reducing PCDD/F formation have been tested on both laboratory-and pilot-plant-scales. The alkali earth metal oxides (CaO, BaO and MgO) have been reported to suppress PCDD/F formation from PCP in a laboratory-scale reactor [5,14]. However, the suppressing efficiencies of them is CaO ≈ BaO > MgO.…”
Section: Introductionmentioning
confidence: 98%
“…Liu et al [13] found that CaO not only absorbed and decomposed dioxin precursors, but also absorbed HCl and prevented the formation of Cl 2 from HCl. Qian et al [5] speculated that the effects of basic compounds such as CaO, BaO, and Ca(OH) 2 on PCDD/F formation could be attributed to suppression of PCDD/F formation through acid-base reactions and other physical and chemical interactions between the precursor PCP and basic metal compounds. While Ruokojârvi et al [39] proposed that the urea molecule itself, or NH 3 or HNCO may form the complex with the catalyzing metal.…”
Section: Possible Mechanism Of Synergetic Inhibitionmentioning
confidence: 99%